The captive's position : female narrative, male identity, and royal authority in colonial New England - Toulouse, Teresa (EBL-Schweitzer, 2007)
Reconsidering captivity narratives published between 1682 and 1707, The Captive's Position explores the ways in which two generations of New England Puritan ministers reacted to internal and imperial challenges to colonial authority by seizing upon representations of captive women to negotiate and to shape a distinctive male identity.